In-hospital course of children with COVID-19 infection - Results of the German nationwide inpatient sample - Karsten Keller; Ingo Sagoschen; Volker H. Schmitt; Stefano Barco; Visvakanth Sivanathan; Omar Hahad; Frank P. Schmidt; Christine Espinola-Klein; Stavros Konstantinides; Thomas Münzel; Lukas Hobohm (Public Health in Practice)
Objectives: To date, few large studies of clinical outcomes in pediatric COVID-19 patients have been reported. Study design: Epidemiological study of the German nationwide inpatient study (GNIS). Methods: We used the GNIS to analyze all hospitalized children ≤18 years with confirmed COVID-19 diagnosis in Germany between Jan 1st and December 31st, 2020. Results: Overall, 3360 children aged ≤18 years were hospitalized with COVID-19 infection in Germany in 2020 (49.8 % females). Among these, 1640 (48.8 %) were aged ≤6 years, 504 (15.0 %) 7 - ≤12 years and 1216 (36.2 %) were aged 13 - ≤18 years. Among these 3360 patients, 3.3 % were treated with mechanical ventilation and 0.23 % died in the hospital. The frequency of venous thromboembolism (0.18 %), vasculopathy (0.68 %), multisystem inflammatory syndrome caused by COVID-19 (0.65 %), and diagnosis of myocarditis (0.60 %) were low. Besides pneumonia and acute respiratory distress syndrome, obesity (OR 6.1 [95 %CI 2.1–18.2], P = 0.001), heart failure (OR 17.0 [95 %CI 6.8–42.1], P < 0.001) and acute/chronic kidney failure (OR 9.5 [95 %CI 4.0–22.2], P < 0.001) were independently associated with mechanical ventilation. Acute or chronic kidney failure (OR 41.4 [95 %CI 7.8–218.6], P < 0.001), liver disease (OR 18.8 [95 %CI 2.5–143.3], P = 0.005), and necessity of mechanical ventilation (OR 7.6 [95 %CI 1.2–47.4], P = 0.031) were independent risk factors for case-fatality. Conclusions: In Germany in 2020, hospitalized children aged ≤18 years with COVID-19 infection had a low case-fatality. Heart, liver and renal failure were associated with adverse COVID-19 complications, such as the need for mechanical ventilation or death. Myocarditis, vasculopathy and venous thromboembolism were rare complications in this patient group.